Implementation of Transactional Analysis Counseling in Overcoming Communication Problems of Long Distance Relationship Couples - Torly Amora Jofipasi; Netrawati; Zadrian Ardi; Jon Efendi (Manajia: Journal of Education and Management, 2024)
Currently, many couples are in long distance relationships with their partners, where in a long distance relationship, communication becomes central in a relationship. Long Distance Relationships (LDR) often face challenges in maintaining effective communication quality. The communication that occurs in couples who are in a long distance relationship has a relatively rare intensity of meetings with their partner, because low intensity often causes problems in their relationship. This research aims to explore the effectiveness of Transactional Analysis in overcoming communication problems in LDR couples. The method used includes a literature review related to the topic to be studied. The research results provide knowledge about the application of Transactional Analysis in helping create ideal communication for LDR couples. These findings provide practical insight for LDR couples and serve as a reference for counselors and psychology practitioners in designing interventions that support healthy communication in long-distance relationships.